(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Liver complication is a major concern in the world. Finding out a new way to combat various liver diseases is very much required. Ginger has been reported to have hepato-protective activity. Here we aimed to formulate an oil-based (self-micro emulsifying) powder to improve the hepatoprotective activity of dry powder of Zingiber officinale (Ginger). Four different formulations of self-microemulsifying dry powder were prepared by mixing with different excipients. The formulated powder was characterized for the angle of repose, Hausner ratio and compressibility index. The hepato-protective activity of the formulated powder was evaluated in vivo. All of the parameters tested for powder characterization showed a good response in terms of flow property and compressibility. Formulated powder exhibited a significant decrease (p<0.05) in hepatic enzymes like aspartate transaminase (AST) and alanine transaminase (ALT) in carbon tetrachloride (CCl4) induced hepatotoxic mice compared to fresh ginger powder group which indicates the enhanced hepatoprotective activity of prepared self-micro emulsifying power in hepatotoxicity. Bangladesh Pharmaceutical Journal 26(2): 125-133, 2023 (July)